Resensi Buku:: Faith-Integrated Being, Knowing and Doing: A Study Among Christian Faculty in Indonesia - Viona Evelin Salinding (Sekolah Tinggi Teologi Bandung, 2023)
Sarinah Lo is a lecturer and head of the Master of Christian Education study program at the Bandung Theological College. Sarinah received her Ph.D degree in education from Trinity Theological Seminary, United States. Sarinah wrote this book based on the results of her dissertation which explored the perceptions of Christian teaching staff in Indonesia regarding the integration of faith and science in a more holistic approach which includes: (1) Being - emphasizing the teacher as an integrator, (2) Knowing - namely the teacher's understanding of the relationship between faith and scientific discipline; and (3) Doing – emphasizes the influence of teachers' faith on their educational practices. This book consists of five chapters. The first chapter contains the background, problem formulation, objectives and significance of the research and contains definitions of the terms used in this book. Chapter two contains a literature review regarding history, definitions, approaches, empirical research and challenges in implementing the integration of faith and science. Chapter three covers the research methodology. Chapter four discusses discovery. Finally, chapter 5 contains conclusions and practical implications of the research.